2012
DOI: 10.1177/0194599812444256
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Tonsillectomy and Nasal Surgery in Adult Obstructive Sleep Apnea

Abstract: In selected adult subjects, tonsillectomy with intercurrent nasal surgery should be considered an effective treatment for OSA and may reduce the requirement for continuous positive airway pressure, oral appliances, or further therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,…”
Section: Resultsmentioning
confidence: 99%
“…Tonsil sizes were reported as: hypertrophied, 37,49 large, 31 enlarged, 21,26,43 extremely enlarged, 33 grades 2-4, 40,66 or grades 3-4. 25,35,39,54,59,63…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a current study by Stow et al [16], patients were sub-divided into three groups according to OSA severity (mild RDI 10-25, moderate RDI 25-35, severe RDI > 35). In a current study by Stow et al [16], patients were sub-divided into three groups according to OSA severity (mild RDI 10-25, moderate RDI 25-35, severe RDI > 35).…”
Section: Tonsillectomymentioning
confidence: 93%
“…septoplasty, turbinectomy, polypectomy, turbinoplasty) correlate with a signifi cant reduction in objective OSA indicators, such as the apnoea-hypopnoea index (AHI) or nocturnal oxygen desaturation. Three studies suggested the efficacy of combined nasal and pharyngeal surgery on polysomnography parameters (Li et al 2005 ;Stow et al 2012 ) or snoring (Carroll et al 2012 ). Friedman et al have also suggested that sometimes postoperative polysomnographic data may be worse for mild OSA patients after nasal obstruction relief (Friedman et al 2000 ).…”
Section: Surgical Managementmentioning
confidence: 99%